Strategies in Structure and Electrolyte Design for High‐Performance Lithium Metal Batteries. (8th February 2021) - Qin, Kaiqiang; Holguin, Kathryn; Mohammadiroudbari, Motahareh; Huang, Jinghao; Kim, Eric Young Sam; Hall, Rosemary; Luo, Chao
Abstract: Lithium metal is the "holy grail" anode for next‐generation high‐energy rechargeable batteries due to its high capacity and lowest redox potential among all reported anodes. However, the practical application of lithium metal batteries (LMBs) is hindered by safety concerns arising from uncontrollable Li dendrite growth and infinite volume change during the lithium plating and stripping process. The formation of stable solid electrolyte interphase (SEI) and the construction of robust 3D porous current collectors are effective approaches to overcoming the challenges of Li metal anode and promoting the practical application of LMBs. In this review, four strategies in structure and electrolyte design for high‐performance Li metal anode, including surface coating, porous current collector, liquid electrolyte, and solid‐state electrolyte are summarized. The challenges, opportunities, perspectives on future directions, and outlook for practical applications of Li metal anode, are also discussed. Abstract : This review summarizes recent advances in stabilizing Li metal anodes via four effective strategies, including surface coating, porous current collector, liquid electrolyte, and solid‐state electrolyte. The aim is to provide a thorough and comprehensive overview of the recent development and applications of Li metal anodes to guide the future study of high‐safety, high‐stability, and high‐energy Li metal batteries.